Comparing the long-term clinical and economic impact of ofatumumab versus dimethyl fumarate and glatiramer acetate in patients with relapsing multiple sclerosis: A cost-consequence analysis from a societal perspective in Germany. Issue 1 (January 2022) - Koeditz, Dominik; Frensch, Juergen; Bierbaum, Martin; Ness, Nils-Henning; Ettle, Benjamin; Vudumula, Umakanth; Gudala, Kapil; Adlard, Nicholas; Tiwari, Santosh; Ziemssen, Tjalf
Background: Evidence suggests that early highly efficacious therapy in relapsing multiple sclerosis is superior to escalation strategies. Objective: A cost-consequence analysis simulated different treatment scenarios with ofatumumab (OMB), dimethyl fumarate (DMF) and glatiramer acetate (GA): immediate OMB initiation as first treatment, early switch to OMB after 1 year on DMF/GA, late switch after 5 years or no switch. Methods: An EDSS-based Markov model with a 10-year time horizon was applied. Cycle transitions included EDSS progression, improvement or stabilization, treatment discontinuation, relapse or death. Input data were extracted from OMB trials, a network meta-analysis, published literature, and publicly available sources. Results: The late switch compared to the immediate OMB scenario resulted in a lower proportion of patients with EDSS 0–3 (Δ − 7.5% DMF; Δ − 10.3% GA), more relapses (Δ + 0.72 DMF; Δ + 1.23 GA) and lower employment rates (Δ − 4.0% DMF; Δ − 5.6% GA). The same applies to late versus early switches. No switch scenarios resulted in worse outcomes. Higher drug acquisition costs in the immediate OMB and early switch scenarios were almost compensated by lower costs for patient care and productivity loss. Conclusion: Immediate OMB treatment and an early switch improves clinical and productivity outcomes while remaining almost cost neutral compared to late or no switches.